2016
DOI: 10.5137/1019-5149.jtn.16263-15.1
|View full text |Cite
|
Sign up to set email alerts
|

Postlaminectomy bone and scar formations in presence of ankaferd blood stopper and bitter melon (momordica charantia); an experimental study

Abstract: ABSTRACTobserved after laminectomy and revealed by magnetic resonance imaging (MRI) (22). Recently, more attention has been focused on PF, which may be responsible for recurrent pain after laminectomy (9,16) to prevent post laminectomy scarring and to induce new bone formation in different approaches (5,8,30). A number of synthetic and natural materials have been used to prevent or reduce PF and induce new bone formation after laminectomy in both animal and human studies (22). Especially, the PASS principles (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Sections were subjected to haematoxylin‐eosin (HE), safranin O/fast green (SOFG) and Masson's trichrome histological stainings, according to conventional procedures 8 , 29 and using standard HE, SOFG and Masson dye solutions (Wuhan Servicebio Technology Co., Ltd.). Microscope images were kept at different magnifications, using a scanning imaging system (ECLIPSE E100 and DS‐U3, NIKON).…”
Section: Methodsmentioning
confidence: 99%
“…Sections were subjected to haematoxylin‐eosin (HE), safranin O/fast green (SOFG) and Masson's trichrome histological stainings, according to conventional procedures 8 , 29 and using standard HE, SOFG and Masson dye solutions (Wuhan Servicebio Technology Co., Ltd.). Microscope images were kept at different magnifications, using a scanning imaging system (ECLIPSE E100 and DS‐U3, NIKON).…”
Section: Methodsmentioning
confidence: 99%
“…Kuruoğlu et al used MC extract in their study to improve bone and connective tissue stroma degeneration following experimental laminectomy. The researchers reported that MC extract application has been useful following bone and connective tissue injury, and the effect possibly resulted from increased collagen biosynthesis and TGF-β levels [Kuruoglu et al, 2017]. Previous studies have reported that treatment with MC significantly enhanced wound closure in diabetic rats and upregulated TGF-β expression in wounds, playing an essential role in regulating cell growth and differentiation [Hussan et al, 2014].…”
Section: Discussionmentioning
confidence: 99%
“…In previous histological studies investigating the effects of ABS on the bone tissue, it was found to have an acceleratory effect on the short-term bone healing process in samples taken on the 7th postoperative day [16,27]. Recently, Kuruoğlu et al (2017) evaluated the late effects of the combination of ABS and β-tricalcium phosphate (TCP) using immunohistochemical methods and they found the bone healing effects of ABS hemostat in their study [17]. Afterwards, Tanık et al (2018) also investigated the late period effects of the combination of ABS and β-TCP on the regeneration of bone tissue in rats [29].…”
Section: Discussionmentioning
confidence: 99%